The Regulatory Role of EvfG Through Coordinated Control of Flagellar Biosynthesis and Energy Metabolism in Porcine Extraintestinal Pathogenic Escherichia coli (ExPEC) - Bingbing Zong; Peiyi Wang; Wei Liu; Aihua Wu; Yong Xiao; Shulin Fu; Yinsheng Qiu; Yanyan Zhang; Wentong Liu (Biology, 2025)
In this study, we found that the deletion of the gene evfG in the type VI secretion system (T6SS) gene cluster significantly affected the motility of porcine extraintestinal pathogenic Escherichia coli (ExPEC) strain PCN033. Furthermore, the bacterial motility assay showed that ΔevfG mutants exhibited reduced motility compared to the parental strain. Transmission electron microscopy (TEM) showed a significant reduction in the number of flagella in the mutant ΔevfG when compared with PCN033. To further explore the reasons why the deletion of evfG affects the motility of PCN033, transcriptomic and metabolomic analyses were conducted. The omics analyses showed that 134 differentially accumulated metabolites and 2236 differentially expressed genes were identified between the mutant ΔevfG and the parental strain PCN033. The metabolome profile and functional annotation analyses indicated that the impaired motility of ΔevfG was connected to the downregulation of the expression levels of genes associated with the energy metabolism pathway and flagellar assembly. Our study provides a new insight into the diminished PCN033 motility induced by evfG deletion. Moreover, the candidate genes and metabolites regulated by the gene evfG in the T6SS, which was involved in the motility of PCN033, were reported in this study.